Angiopoietin-2 level as a tool for cardiovascular risk stratification in hypertensive type 2 diabetic subjects. Issue 4 (19th May 2018) - Siddiqui, Khalid; Joy, Salini Scaria; Nawaz, Shaik Sarfaraz; Al Otaibi, Mohammad T.; Al-Rubeaan, Khalid
ABSTRACT: Objectives : This observational cross-sectional study aimed to investigate the relationship between serum Angiopoietin-2 (Ang-2) levels and cardiovascular (CVD) risk factors in drug controlled hypertensive diabetic subjects without cardiovascular complications. Methods : All subjects were evaluated for fasting blood glucose (FBG), HbA1c, liver enzymes, lipid profile and serum Ang-2. Results : Mean serum Ang-2 level was significantly higher in hypertensive diabetic subjects. In bivariate analysis in diabetic subjects with cardiovascular risk factors, Ang-2 positively correlated with waist circumference, body mass index (BMI), systolic blood pressure (SBP), FBG, HbA1c and triglycerides. In multivariate linear regression analysis, this association remained significant with FBG and triglycerides. Ang-2 levels were independently associated with CVD risk factors in drug controlled Type 2 diabetes (T2D) subjects. Conclusions : Further detailed studies in larger population with more attention is needed to consider Ang-2 level as a tool for CVD risk stratification in hypertensive diabetic subjects.